2020
DOI: 10.1177/2309499020926790
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal thromboprophylaxis in low-risk patients undergoing lower limb arthroplasty: A retrospective observational cohort analysis of 1400 patients with ultrasound screening

Abstract: Purpose: This study reports the results of a multimodal thromboprophylaxis protocol for lower limb arthroplasty involving risk stratification, intraoperative calf compression, aspirin prophylaxis and early (within 4 h) post-operative mobilisation facilitated by the use of local infiltration analgesia. The study also aimed to identify risk factors for venous thromboembolism (VTE) within a 3-month period following surgery for patients deemed not at elevated risk. Methods: Patients undergoing knee/hip arthroplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…In addition, in our study, all DVTs were distal type. Some studies also found that the incidence of distal DVT after orthopedic surgery was significantly higher than that of the proximal [ 23 , 24 ]. This may be related to the greater effect of tourniquet on venous blood stasis in distal limbs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in our study, all DVTs were distal type. Some studies also found that the incidence of distal DVT after orthopedic surgery was significantly higher than that of the proximal [ 23 , 24 ]. This may be related to the greater effect of tourniquet on venous blood stasis in distal limbs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors provided specific data for the additive value of mechanical compression in combination with pharmacologic prophylaxis and reported a decrease in the incidence of symptomatic pulmonary embolism (PE) from 2.92% to 1.20% when comparing pharmacological prophylaxis alone to combined mechanical compression and pharmacological prophylaxis (95% confidence interval, 0.23 to 0.64). While Harrison-Brown et al, An et al ., and Torrejon et al, also argued in support of the synergistic role of chemical prophylaxis in combination with mechanical compression, their reports did not demonstrate any additive value of mechanical compression in combination with pharmacologic prophylaxis 454-456 .…”
Section: - Should Mechanical Compressive Devices Be Used Routinely In...mentioning
confidence: 90%
“…Venous thromboembolism (VTE) is a serious complication following lower limb arthroplasty (LLA) that can lead to significant morbidity and potential mortality. The reported rate of VTE following LLA is around 1% [ 1 , 2 ]; rates reported in the literature vary between 0.77 and 6.6% [ 3 , 4 ]. It is well understood that the three factors noted in Virchow’s triad (impaired blood flow, hypercoagulability and endothelial damage) are affected by orthopaedic surgery through factors such as the use of a tourniquet and immobilisation causing venous stasis, endothelial damage secondary to surgery and hypercoagulability secondary to inflammation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%